In Vitro Anti-inflammatory Activity of Extract and Fraction Seed Coat Kebiul (Caesalpinia bonduc L.) - Raden Fatahillah; Dwi Fitriyani; Fitria Wijayanti (Al-Kimia, 2022)
Inflammation is the protective reaction of body and supporting element of tissues to injurious stimuli, such as physical injury, tissue and cell damage by pathogens, and protein denaturation. This study aims to compare the antiinflammatory activity of ethanol extract, ethanol fraction, and n-hexane fraction from kebiul (Caesalpinia bonduc L.) seed coat. Antiinflammatory activity was tested by measuring the % inhibition of the denatured protein using a UV-Vis spectrophotometer. From the result of the study obtained IC50 value 2,10 μg/mL, 7,89 μg/mL, 4,04 μg/mL & 11,03 μg/mL.